MANAJEMEN PEMASARAN MELALUI SOSIAL MEDIA BAGI LEMBAGA PENDIDIKAN : Studi Social Media Marketing STMIK Komputama Majenang - Kuswantoro (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2020)
In order to introduce STMIK Komputama Majenang to the community both in Central Java Province, Indonesian society and the world community, it is necessary to have good promotion efforts through the internet. Website, blog, and social media as facilities that can be used for media promotion. Social media can be used to socialize work programs, socialize policies, introduce programs, improve the image of institutions, and as a means of learning for the wider community about educational institutions. The object of research in this paper is the STMIK Komputama Majenang social media account. Using the case study method, this research concludes that social media as an effective and efficient promotional tool really helps marketing activities for STMIK Komputama Majenang.Key Words: Social Media Marketing, STMIK Komputama Majenang